Water supply to lettuce by capillary rise of the water table - Martins Araújo, Eliakim; Távora Costa, Raimundo Nonato; Gonçalves Nunes, Kenya; Oliveira da Silva, Alexsandro; Carvalho de Sousa, Carlos Henrique; Martins Araújo, Efraim (Revista Brasileira de Engenharia de Biossistemas, 2023)
Brazil has significant potential for floodplain areas which are suitable for cultivation after the rainy season, with water supply from the water table. Short-cycle crops with shallow root systems are more suitable for these conditions. On this subject, the objective of this study was to determine the responses of the lettuce crop to rising damp rates and water table depth levels. The variables of production, gas exchange, and SEW30 values (sum of excess water above 0.30 m depth) were analyzed. A physical model of seven drainage lysimeters was used; in six, the only water supply occurred by capillary rise from the water table (0.10; 0.15; 0.20; 0.25; 0.30 and 0.35 m depth) and, in the remaining lysimeter, irrigation was performed with no water table. The water table level maintained at 0.20 m from the soil surface was able to supply the water demanded by a sandy soil. The factor-product ratio indicates this depth as the most viable option in terms of crop response. Among the analyzed cultivars and under conditions of excess water in the soil, preference should be given to the establishment of the Gloriosa cultivar, for higher yields.